Determination of crop dynamic and aerodynamic parameters for lodging prediction. Issue 202 (July 2020) - Joseph, G.M.D.; Mohammadi, M.; Sterling, M.; Baker, C.J.; Gillmeier, S.G.; Soper, D.; Jesson, M.; Blackburn, G.A.; Whyatt, J.D.; Gullick, D.; Murray, J.; Berry, P.; et al.
Abstract: This paper considers a process through which the wind costs the agricultural industry hundreds of millions of pounds per year - crop lodging. Lodging is the displacement of crops by wind (and rain) that can result in either stem breakage or uprooting. In particular this paper builds upon recent work to develop a generalised model of the lodging process and presents the results of several experimental campaigns to identify dynamic and aerodynamic parameters that are required as inputs to the model in order to estimate lodging wind speeds. These experiments were carried out at various sites in the UK and the Republic of Ireland to determine the natural frequencies, damping ratios and drag areas of maize, oats and oil seed rape. The experimental methodology, which was based upon the tracking of plant displacements, was shown to be robust, and consistent values of the parameters were obtained, albeit with much larger experimental uncertainties than would normally be expected in wind engineering applications. The values of these parameters were also consistent with those of earlier measurements for wheat. The generalised model was then used to determine lodging wind speeds for the three crops, and an assessment was made of the effect of experimental uncertainties in dynamic, aerodynamic and agronomic variables on the predicted values. In broad terms the generalised lodging model was shown to well describe the crop behaviour for isolated crops, and it was shown that it could be used in a simplified form for interlocked crop canopies. It was also shown that uncertainties in the aerodynamic parameters resulted in uncertainties of around an order of magnitude in lodging risk, whilst typical variations between plants in some crop parameters (notably stem strength and radius) could result in lodging risk uncertainties of two orders of magnitude. Highlights: Experiments to measure crop dynamic and aerodynamic parameters in high winds, to calibrate analytical lodging model. A novel method of plant displacement measurement using video tracking of individual plants. A comparison of natural frequencies, damping ratios and drag are for oats, maize, oil seed rape, and wheat. Determination of lodging wind speeds and lodging risk for the different crops.